Does the MRCGP examination discriminate against Asian doctors?. Issue 6845 (11th July 1992) - Wakeford, R.; Farooqi, A.; Rashid, A.; Southgate, L.
Abstract : OBJECTIVE–To ascertain whether the membership examination for the Royal College of General Practitioners (MRCGP) discriminates against doctors of Indian subcontinent ethnic origin ("Asian doctors"). DESIGN–Retrospective analysis of data from five administrations of the MRCGP examination (December 1988-December 1990). SETTING–United Kingdom national examination body. SUBJECTS–3686 doctors taking the examination for the first time, 244 of whom were classified as Asian, the remainder as non-Asian. MAIN OUTCOME MEASURES–Comparison of performance in each of the written and oral components of the examination between Asian doctors, identified by their names and classified into subgroups by countries of birth and primary medical training from data provided at registration, and non-Asian doctors. RESULTS–On written components of the examination (multiple choice paper mean score Asians versus non-Asians 42.3 v 48.6, modified essay paper 40.9 v 48.9, practice topic/critical reading paper 41.5 v 48.7, all p less than 0.001 by t testing). But analysis by countries of birth and primary training showed that these differences were due largely to poor performance by certain groups of Asian doctors, especially those born and trained in the Indian subcontinent or elsewhere outside the United Kingdom. Asian doctors born and trained in the United Kingdom and those born in Africa or the West Indies and trained in the United Kingdom performed similarly to the non-Asian doctors. CONCLUSIONS–The examination does not systematically discriminate against Asian doctors, but the poor performance of the two subgroups of Asians is cause for serious concern and requires investigation.